The Effect of STEAM Approach in Physics Learning to Enhance 21st Century Skills : A Literature Review - Azizatul Nur Rohmah; Nurita Apridiana Lestari; Hanandita Veda Saphira (Journal of Digitalization in Physics Education, 2025)
Objective: The STEAM approach has an important role in improving 21st-century skills in students so that it can prepare them to face future demands. This study aims to analyze the effect of the STEAM approach in physics learning on improving 21st-century skills. Method: This study is literature research with a qualitative approach that uses national and international journals as data sources. Data were collected through Google Scholar and Scopus, and as many as 20 journal articles related to the STEAM approach in physics learning were published in 2020-2024. The data were analyzed using qualitative descriptive analysis through literature study. Results: Based on the research results, using the STEAM approach has a significant positive impact on various 21st-century skills, including creativity, concept understanding, critical thinking, argumentation skills, and problem-solving. Among these skills, creative thinking skills were the most measured. In addition, the STEAM approach is often integrated with learning models such as STEAM Learning and Project-Based Learning (PjBL). These findings confirm the effectiveness of the STEAM approach in developing comprehensive skills in students. Novelty: This research is expected to provide strategic insights for educators in designing innovative and practical learning, especially by utilizing the STEAM approach to support the needs of 21st-century education.